Cognitive fusion and depressive symptoms in women with chronic pain: A longitudinal growth curve modelling study over 12 months. (9th July 2019) - Carvalho, Sérgio A.; Trindade, Inês A.; Gillanders, David; Pinto‐Gouveia, José; Castilho, Paula
Abstract: This study aims to (a) explore individual differences in women with chronic pain (CP) in regard to pain intensity, functional impairment, cognitive fusion, and depressive symptoms and (b) longitudinally test whether cognitive fusion is a significant predictor of depression symptoms, while controlling for pain intensity and functional impairment, over a 12‐month period. This study follows a longitudinal design and was conducted in a sample of 86 women with CP who responded to an online battery of questionnaires in three equally spaced assessment moments. In order to explore the growth trajectory of variables of interest, latent growth curve models were examined. Also, correlation analyses were conducted between demographic and illness‐related variables and depressive symptoms, as well as between all variables in all assessment moments. Cognitive fusion and functional impairment (but not pain intensity) were significantly associated with baseline levels of depressive symptoms. Cognitive fusion significantly predicted the growth trajectory of depressive symptoms, whereas pain intensity and functional impairment did not. No demographic (age, marital status, education, socio‐economic) nor illness‐related variables (number of CP diagnoses, duration of CP, taking medication) were associated with depressive symptoms at any point. These results suggest that the trajectory of depressive symptoms in women with CP is not predicted by the intensity of pain nor pain‐related functional impairment, but rather by the tendency to get entangled with internal experiences (e.g., thoughts, emotions, and physical sensations), which may or may not be related to pain‐specific contents. Clinical implications are discussed.